Evaluation and comparison of Awareness and practice of protective measures for COVID-19 between preclinical and clinical Medical students in developing country: Pakistan - Mukhtar, Ahmad; Hussain, Mukhtar; Tariq, Naila; Mukhtar, Rubina (Technium Social Sciences Journal, 2021)
Objective of this study was to evaluate the awareness and practice of medical students for preventive measures and to compare Covid related knowledge between preclinical and clinical students. Materials and methods: It is an observational cross section study conducted in medical students of southern Punjab, Pakistan. A questionnaire consisting questions for demographic, COVID -19 related information and practice for preventive measures was given online and response of students was recorded and result was analyzed. Results: Out of 589 students 230 (39%) were males and 359 (61%) were females. Over all 85% students were well aware of virology, predisposing factors and preventive measures Clinical students were having more knowledge as compare to pre clinical students. Male students were better aware of covid-19 as compare to female students. The most common source of information was social media. Practice of preventive measure was better by clinical students. Good awareness and preventive practice in clinical students might be based on fact of direct dealing or contact with Corona patients in wards. Moreover observing the intensive treatment required for symptomatic patients and poor outcome in some patients increases the Covid fear or anxiety that increases the thirst for gaining more information and knowledge. Conclusion: There is inadequate knowledge overall among preclinical and female students. Awareness for covid-19 pandemic has key role in control of Covid pandemic and its related fear and anxiety in medical students but unfortunately is an ignored aspect in developing countries. There is need of intervention by public health department for designing curriculum and education plans.